Factors influencing suicidal ideation among Chinese patients with stomach cancer: qualitative study. (20th December 2016) - Zhang, X.K.; Procter, N.G.; Xu, Q.; Chen, X.Y.; Lou, F.L.
Abstract : Aim: The aim of this qualitative descriptive study was to explore the influencing factors of suicidal ideation in Chinese patients diagnosed with stomach cancer. Introduction: More recently, links have been made between suicide and cancer. For inpatients with cancer, nurses are at the front line to cope with suicidal issues in clinical settings. Method: This study was part of a larger study that investigated psychological strains and related factors associated with suicidal ideation. Thirty‐two patients with stomach cancer participated in a face‐to‐face interview. Thematic analysis was used to analyse the qualitative data. Findings: Four themes were identified as protective factors against suicidal ideation: suicidal denial and fears of stigmatization; positive coping skills; family connectedness; and desire to live well and longer. Discussion: Consistent with previous research, these four protective factors may encourage participants to think more positively about life and cancer. Conclusion: Our findings suggest four protective factors for targeted suicide prevention, which may play an important role in future suicide‐prevention programmes for Chinese patients diagnosed with stomach cancer. Implications for nursing: Nurses may help reduce patients' risk for suicidal ideation more effectively by discussing beliefs, family and meaning in life perspectives, as well as offering health education about positive coping skills. Implications for healthy policy: Clinical nurses, hospitals and the government should work collaboratively with each other. It is suggested that Chinese national guidelines for working with the high‐risk suicide populations should be considered within a future mental health working plan.